Detection and decontamination of Mycobacterium chimaera and other non-tuberculosis mycobacteria in heater–cooler devices used in cardiopulmonary bypass: a Manufacturer and National guidelines summary, and a potential resolution to the problem requiring further investigation. (April 2020) - Casini, Beatrice; Tuvo, Benedetta; Totaro, Michele; Baggiani, Angelo; Privitera, Gaetano
Since 2011, invasive infections due to Mycobacterium chimaera have been diagnosed in patients with previous cardiac surgery. The use of heating/cooling devices (heater–cooler units), necessary to regulate the blood temperature in extra-corporeal circulation, has been identified as a source of contaminated aerosol. Adhering to a strict maintenance program according to the manufacturer's instructions for use including sanitizing is essential to reduce the risk. Current manufacturer guidelines and national recommendations for detection and decontamination of Mycobacterium chimaera and other non-tuberculosis mycobacteria should organically update units' policies and protocols as they are published.